Bedmar & Shi : romancing the tropics - Riera Ojeda, Oscar (Singapore : Published [and] distributed by Page One Pub., 2007)
Architect-designed houses in Singapore
Keywords: Bedmar & Shi (Firm; Architect-designed houses -- Singapore -- 20th century; Architect-designed houses -- Singapore -- 21st century; Architecture -- Singapore -- 20th century; Architecture -- Singapore -- 21st century; Dwellings -- Singapore